Multilineage-differentiating stress-enduring cells: a powerful tool for tissue damage repair - Que, Hanyun; Mai, Erziya; Hu, Yanting; Li, Hong; Zheng, Wenxin; Jiang, Yuchen; Han, Feiruo; Li, Xuedong; Gong, Puyang; Gu, Jian (Frontiers in Cell and Developmental Biology, 2024)
Multilineage-differentiating stress-enduring (Muse) cells are a type of pluripotent cell with unique characteristics such as non-tumorigenic and pluripotent differentiation ability. After homing, Muse cells spontaneously differentiate into tissue component cells and supplement damaged/lost cells to participate in tissue repair. Importantly, Muse cells can survive in injured tissue for an extended period, stabilizing and promoting tissue repair. In addition, it has been confirmed that injection of exogenous Muse cells exerts anti-inflammatory, anti-apoptosis, anti-fibrosis, immunomodulatory, and paracrine protective effects in vivo. The discovery of Muse cells is an important breakthrough in the field of regenerative medicine. The article provides a comprehensive review of the characteristics, sources, and potential mechanisms of Muse cells for tissue repair and regeneration. This review serves as a foundation for the further utilization of Muse cells as a key clinical tool in regenerative medicine.